PERAN GURU SEBAGAI FASILITATOR PEMBELAJARAN DARING PADA PANDEMI COVID-19 - Siti Yuliani; Rusi Rusmiati Aliyyah; Iyon Muhdiyati (Khazanah Pendidikan, 2022)
This study aims to determine the role of online learning facilitator teachers during the pandemic at SDN Cimande 01 using a qualitative approach with the case study method. Data collection techniques were carried out through observation, questionnaires, interviews and documentation. The research respondents consisted of 1 teacher, 23 parents and 23 grade VI elementary school students. The data analysis procedure uses the Miles and Huberman model, namely reduction, data presentation, and drawing conclusions. Validity check using source and technique triangulation. The results showed that the teacher's role as a facilitator of online learning during the pandemic was carried out through the use of information and communication technology (ICT) through WhatsApp, Google Meet and Google Classroom. Learning videos are used as learning media. The learning methods used in online learning are question and answer, discussion and assignments. The inhibitory factors for teachers as facilitators are students, who are associated with the lack of availability of their smartphones, adding an internet quota while learning, and an unstable internet network.